Urgensi Mata Rantai Keilmuan dalam Pendidikan Islam di Era AI - Nur Syafaat, Imron; Darwis, Mohammad; afnan fajaruddin, ahmad (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study explores the urgency of the chain of knowledge transmission (sanad) in Islamic education in the era of artificial intelligence (AI). Sanad, as an authoritative mechanism for transmitting knowledge, remains relevant and essential in preserving the authenticity and integrity of Islamic teachings. The integration of AI in Islamic education offers opportunities to enhance accessibility and personalized learning but also presents challenges related to potential misinformation and the degradation of human interaction. This research employs a qualitative approach with a focus on a comprehensive literature review to analyze and synthesize relevant sources. The findings indicate that AI can be utilized to strengthen rather than replace the role of teachers and the sanad system. Therefore, this study recommends the development of a comprehensive framework to guide the integration of AI in Islamic education, emphasizing ethics, transparency, and accountability. This framework should also include guidelines for curriculum development, teacher training, and students’ digital literacy. By doing so, Islamic education can bridge the gap between tradition and technology, preparing young Muslim generations to face global challenges without compromising the core values of the sanad system.